Le dit et le non-dit dans Diable, Dieu et autres contes de menterie de Pierre Gripari - Komandera, Aleksandra (Romanica Silesiana)
In her text devoted to the science-fiction literature, predestined to create the aura of understatement by nature, Aleksandra Komandera concentrates on the works written by Gripari. Keywords: fantastique; magic realism; fantasy; genre; category; the supernatural; unexplained / inexplicable phenomena; hesitation